Potensi Media Transport Modifikasi Sebagai Penunjang Pemeriksaan Kultur Bakteri - Patricia, Venny; Yani, Ahmad; Nur fathonah, Amanda Kukuh (Jaringan Laboratorium Medis, 2024)
Bacterial culture sample transport is a critical point in the culture chain from sampling to final diagnosis. The ideal transport medium should be able to nurture the ability of bacteria to thrive coming from the sample without allowing them to grow. Transport media that already exist in Indonesia, namely in the form of powder, tend to be very expensive in price and transport media that can be used directly besides being expensive have a fast expiration period, which will increase the cost of treatment and services in hospitals, an innovation is needed by making alternative transport media from materials that are easily available around us that can be useful for taking samples. The purpose of this study is to see the potential of alternative transport media so that it can support diagnostics in bacterial culture. The study method uses an experimental laboratory with a true-experimental post-test-only design. In testing alternative transport media, sampling from diabetic foot ulcer patients using tofu pulp transport media (MTAT) and ICU swab beds with coconut charcoal transport media (MTAK). Samples of each media were taken, and as many as 20 samples were taken. In addition to treatment samples, each sample is confirmed using standard transport media as its control. This study obtained dominant bacteria from diabetic ulcer samples on alternative MTAT Citrobacter sp 6 (30%) and Control Citrobacter sp 8 (40%). Meanwhile, the ICU swab bed samples obtained dominant bacteria MTAK Bacillus sp 10 (50%) and Control 11 (55%). The conclusion of these two alternative transport media can be used as alternative transport media because they have the same growth results compared to standard media, and it can be ascertained that it is really bacteria that usually grow without contamination.